Associations Between Community-Level Racial Biases, Office Discipline Referrals, and Out-of-School Suspensions. Issue 2 (3rd July 2021) - Girvan, Erik J.; McIntosh, Kent; Santiago-Rosario, Maria R.
Abstract: This study examined the extent to which disparities in Black and White students' risks of receiving office discipline referrals (ODRs), and out-of-school suspensions (OSSs) were related to differences in implicit and explicit racial biases assessed at the community level. The sample consisted of discipline records for 1, 354, 010 students enrolled in 2, 100 U.S. schools in 183 communities distributed across the United States. Analyses estimated and compared the contributions of average implicit and explicit racial biases in schools' localities to school-level disproportionality in ODRs, OSSs, and OSSs controlling for disproportionality in ODRs. Results showed that community-level racial biases were related to racial disparities in ODRs and OSSs in schools, with some important differences by type of discipline decision. Impact Statement This study provides evidence that community-level explicit and implicit racial biases are associated with school-level racial disproportionality. Results indicate that a significant proportion of racial disproportionality may result from the effects of bias on the decision to issue an office discipline referral, as opposed to the decision tosuspend a student, indicating that a focus on classroom systems has the strongest potential to increase equity in school discipline. Supplemental data for this article can be accessed online at https://doi.org/10.1080/2372966X.2020.1838232